Identification of Indicators for Evaluating Reclamation and Post-Mining Policies Towards Compliance by Companies in Jambi Province in Environmental Aspects - Amril Fadli; Bunga Mardhotillah (Edujavare Publishing, 2026)
Mining activities in Jambi Province significantly contribute to economic growth but pose severe threats to environmental sustainability. Despite existing regulations, company compliance regarding reclamation and post-mining obligations remains a critical challenge. Evaluating these policies requires a clear, standardized set of indicators to measure compliance effectively. This study aims to identify and formulate key performance indicators (KPIs) for evaluating reclamation and post-mining policies, specifically focusing on enhancing company compliance with environmental aspects in Jambi Province. This study employs a mixed-methods approach combining qualitative and quantitative analyses. Data were gathered through legal desk research, deep interviews with environmental experts, government officials, and mining representatives, followed by a Delphi survey to validate the indicators. The Analytical Hierarchy Process (AHP) was utilized to prioritize and weight the identified indicators. The study successfully identified four main dimensions of indicators: Ecological Restoration (soil quality, revegetation success, biodiversity index), Financial Assurance (reclamation bond placement, budget realization), Legal-Administrative Compliance (reporting punctuality, document conformity), and Social-Environmental Impact (acid mine drainage control, local community satisfaction). Ecological restoration and financial assurance emerged as the highest-weighted priorities for ensuring long-term environmental sustainability. The formulated indicators provide a robust, measurable framework for local governments to monitor, audit, and evaluate mining companies' compliance. Implementing these structured indicators will strengthen policy enforcement and accelerate successful post-mining rehabilitation in Jambi Province.